OPTIMALISASI TATAKELOLA SAMPAH BERBASIS BUDIDAYA MAGOT UNUTK PENGUATAN EKONOMI SIRKULAR DI DESA NGIJO - Jeny Ernawati Tambunan; Dhira Khurniawan Saputra; Fahreza Okta Setyawan; Akhmad Zainuri; Ubaidillah Ubaidillah; Astried Vanessa; M. Nadhif; Sevia Medytya; Naila Nency; Aisah Girindra; Althofian Arya; Shefita Meilana; Vira Nur Titisari; Shalma Dinda; Gading Mahendra; Agustinus Agustinus; Muhammad Ridha (Universitas Mataram, 2023)
Ngijo Village experienced an increase in household waste which made waste management in Ngijo Village difficult. This community service activity is motivated by the increase in waste volume due to the increasing settlement and population activities in Ngijo Village. The solution to dealing with waste problems uses the circular economy concept in waste management. The circular economy concept focuses on reusing waste as raw materials for production and reducing final waste discharged into the environment. Purpose of activity: This is what underlies the importance of this service activity which aims to implement a circular economy and assist Ngijo Village's priority program regarding waste management based on magot cultivation. Method: The method used is a community empowerment approach involving students participating in the Brawijaya University MMD KKN. Service is carried out in the form of workshops and practice or training. The evaluation process at the end of the activities that have been carried out involves partners so that they can develop following the main aspects outlined in the solution offered. Results: Through this service activity, the Ngijo village community has the knowledge and ability about the importance of waste management based on maggot cultivation, carrying out a business feasibility analysis for fish/catfish cultivators using maggots as natural food. Conclusion: The conclusion of this activity is that the goal of reducing organic waste was achieved by optimizing maggot cultivation and the results of the feasibility analysis of the catfish cultivation business at the Ngijo Village TPST were declared feasible by looking at management, marketing, legal, socio-cultural, technical and operational, and financial aspects.